Boost derived hybrid converter:problem analysis and solution - Vakacharla V.R.; Chauhan A.K.; Reza M.M.; Singh S.K. (My University, 2025)
Generating DC and AC voltage from a single DC input, through single stage conversion is cardinal for nanogrid applications. A boost derived hybrid converter is one of the topology used for nanogrid application, which works well in continuous mode of operation rendering both the dc and ac load simultaneously. Despite of this converters successful performance in continuous conduction mode, undesirable results come in to picture in case discontinuous mode and standalone AC operation. This paper focusses on providing the solution for above mentioned problems to stabilise operation in both conditions thus ensuring reliable operation of the converter under wide load ranges. 2016 IEEE.